The Influence of Zakat Knowledge, Tax Knowledge, and Religius on Zakat As a Tax Reduction in The City of Banda Aceh - Hafidhah Hafidhah; Cut Dian Fitri; Havna Havna (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research is motivated by Muzakki's perception of Zakat as a tax deduction in Banda Aceh City. This goal can be achieved with various strategies, including increasing knowledge of Zakat, Taxes, and Religiosity in the people of Banda Aceh City. This study measures Muzakki's perceptions of Zakat as a tax deduction in Banda Aceh City. The population in this study was 175 civil servant respondents at the Banda Aceh City Hall office. The data is processed using Structural Equation Modeling (SEM) to determine the effect of the variables. The study results show that Knowledge of Zakat positively and significantly affects Zakat as a tax deduction. The influence of tax knowledge has no significant effect on Zakat as a tax deduction. Religiosity has a positive and significant effect.